Experimental Investigation of Natural Circulation Stability Phenomena in a New Loop Heat Pipe Model - Wirza, Alif Rahman; Kusuma, Mukhsinun Hadi; Rozi, Khoiri; Kiono, Berkah Fajar Tamtomo; Restiawan, Muhammad Mika Ramadhani; Giarno, Giarno; Pambudi, Yoyok Dwi Setyo; Yunus, Muhammad; ButarButar, Sofia Loren; Hatmoko, Sumantri; Apriandi, Nanang; Pramesywari, Afifa (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2024)
The severe accident at the Fukushima Dai-ichi Nuclear Power Plant in Japan in 2011 highlighted the critical need for a passive cooling system to dissipate residual decay heat following the failure of active cooling systems in the nuclear facility. The loop heat pipe (LHP) is a promising technology for such applications. The objective of this research is to understand the natural circulation stability phenomena of new LHP model under varying conditions of filling ratio and heat load. The experimental methodology employed a laboratory-scale LHP model made of copper with an inner diameter of 0.104 m. The experiments were designed with filling ratios of 20%, 40%, 60%, 80%, and 100%, and hot water temperature as the evaporator heat source with variations of 60°C, 70°C, 80°C, and 90°C. The initial operating pressure was 10665.6 Pa, with a 5˚ inclination angle, demineralized water as the working fluid, and cooled by air at a velocity of 2.5 m/s. The results show that the natural circulation within the LHP occurs in two phases and maintained stability, with optimal performance observed at an 80% filling ratio and 90°C. The conclusion of this research indicates that natural circulation stability in the LHP operates well and occurs in two phases, proving that natural circulation in the LHP is effective in heat dissipation.